Divergent endophytic viromes and phage genome repertoires among banana (Musa) species - Aghdam, Shiva A.; Lahowetz, Rachel M.; Brown, Amanda M. V. (Frontiers in Microbiology, 2023)
Viruses generally cause disease, but some viruses may be beneficial either as resident regulators of their hosts or host microbiomes. Plant-associated viruses can help plants survive by increasing stress tolerance or regulating endophytic communities. The goal of this study was to characterize endophytic virus communities in banana and plantain (Musa spp.) genotypes, including cultivated and wild species, to assess virome repertoires and detect novel viruses. DNA viral communities were characterized by shotgun sequencing of an enriched endosphere extract from leaves and roots or corm of 7 distinct Musa genotypes (M. balbisiana, Thai Black, M. textilis, M. sikkimensis, Dwarf Cavendish, Williams Hybrid, and FHIA-25 Hybrid). Results showed abundant virus-like contigs up to 108,191 bp long with higher relative abundance in leaves than roots. Analyses predicted 733 phage species in 51 families, with little overlap in phage communities among plants. Phage diversity was higher in roots and in diploid wild hosts. Ackermanniviridae and Rhizobium phage were generally the most abundant taxa. A Rhizobium RR1-like phage related to a phage of an endophytic tumor-causing rhizobium was found, bearing a holin gene and a partial Shiga-like toxin gene, raising interest in its potential to regulate endophytic Rhizobiaceae. Klebsiella phages were found that are of interest for possible protection against Fusarium wilt and other phages were predicted with potential to regulate Erwinia, Pectobacterium, and Ralstonia-associated diseases. Although abundant phage-containing contigs were functionally annotated, revealing 1038 predicted viral protein domains, gene repertoires showed high divergence from database sequences, suggesting novel phages in these banana cultivars. Plant DNA viruses included 56 species of Badnavirus and 26 additional non-Musa plant viruses with distributions that suggested a mixture of resident and transient plant DNA viruses in these samples. Together, the disparate viral communities in these plants from a shared environment suggest hosts drive the composition of these virus communities. This study forms a first step in understanding the endophytic virome in this globally important food crop, which is currently threatened by fungal, bacterial, and viral diseases.